Gender stereotypes and social perception of vocal confidence is mitigated by salience of socio-indexical cues to gender - Roche, Jennifer M.; Asaro, Katie; Morris, Bradley J.; Morgan, Shae D. (Frontiers in Psychology, 2023)
, cues that point to some element of the context that aid interpretation) to gender and vocal affect often interact and sometimes lead listeners to make differential judgements of affective intent based on the gender of the speaker. Previous research suggests that rising intonation is a common cue that both women and men produce to communicate lack of confidence, but listeners are more sensitive to this cue when it is produced by women. Some speech perception theories assume that listeners will track conditional statistics of speech and language cues (e.g., lexical choices and the frequency of the socio-indexical cues to gender and affect) in their listening and communication environments during speech perception. It is currently less clear if these conditional statistics will impact listener ratings when context varies (e.g., number of talkers, lexical choices, gender and affective cues). To test this, we presented listeners with vocal utterances from one female and one male-pitched voice (single talker condition) or many female/male-pitched voices (4 female voices; 4 female voices pitch-shifted to a male range) to examine how they impacted perceptions of talker confidence. Results indicated that when one voice was evaluated, listeners defaulted to the gender stereotype that the female voice using rising intonation (a cue to lack of confidence) with negation was less confident than the male-pitched voice (using the same cue). However, in the multi-talker condition, this effect went away and listeners equally rated the confidence of the female and male-pitched voices. Findings support dual process theories of information processing, such that listeners may rely on heuristics when speech perception is devoid of context, but when there are no differentiating qualities across talkers (regardless of gender), listeners may be ideal adapters who focus on only the relevant cues.